PENGARUH PRODUK,HARGA,LOKASI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN - adhe suryaningsih suryaningsih (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aimed to analyze the effect of product, price, location and quality of service individually on consumer purchasing decisions. The study was conducted on Babarsari Branch of Warung Sego Penyet (WSP)customers . The population in this study is the customer Babarsari Branch of Warung Sego Penyet (WSP), with a sample of 97 respondents, drawn by convenience sampling method. Data were analyzed using multiple linear regression analysis that preceded the validity and reliability as well as the classical assumption test consisting of multicoloniarity test, heteroscedasticity test, test for normality. T test results showed variable price and quality of service significant positive effect on consumer purchasing decisions while the variable product and location not significant positive effect on the interest saving. Price variable is the variable that has the most dominant influence on consumer purchasing decisions. Value Adjusted R Square of 0,681